(untitled) (Fiep Bulletin - online, 2017)
The ideal posture is the one that respects the anatomical curves of the spine, pelvic hip and scapular, giving balanceand support to the individual, which should not only aim to the esthetic but also to the decrease of the extra charge over the bodysegments giving functionality to the body. The physical education teachers should advise their students to have the correctposture not only when performing certain activity, but in their daily lives, minimizing possible postural problems that the bad habit,compensations and exercises performed in a wrong way bring. This study is about a bibliographic research with an analyticdescriptivecharacter, which looked for understanding what the importance is and the benefits that corrective exercises have overpostural deviations from prevention to the triggering of them and its applicability in the school environment. Preconized to performa physical evaluation to observe the possible gains and development of the student through the re-evaluation in the end of theschool year.